Day 2 Tue, November 13, 2018 2018
DOI: 10.2118/192762-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Reservoir-Friendly Drilling Fluid for Higher Gas Production

Abstract: Drilling gas reservoir requires high mud density to balance the reservoir pressure. To formulate such fluids, calcium carbonate (CaCO3) was used because of its high acid solubility. However, due to the high concentration of CaCO3 required for high density drilling fluid, sticking might occur which might result in fishing and/or sidetracks operations. To minimize sticking problems, barite (BaSO4) is added with CaCO3 to reduce the amount of solids needed to formulate the drilling fluid. However, barite can cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The experimental results showed that the addition of lignite, vinyl amide, and vinyl sulfonate copolymer prominently improves the rheological features and enhances fluid loss control. 115 The key features of Mn 3 O 4 were exploited by combining with ilmenite to get ultrahigh-density drilling fluid with a density of 22.12 lb/gal. The testing of a Mn 3 O 4 and ilmenite mixture under drastic field conditions of 410 °F and 300 psi proved their stability.…”
Section: High-density Brines As Drilling Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results showed that the addition of lignite, vinyl amide, and vinyl sulfonate copolymer prominently improves the rheological features and enhances fluid loss control. 115 The key features of Mn 3 O 4 were exploited by combining with ilmenite to get ultrahigh-density drilling fluid with a density of 22.12 lb/gal. The testing of a Mn 3 O 4 and ilmenite mixture under drastic field conditions of 410 °F and 300 psi proved their stability.…”
Section: High-density Brines As Drilling Fluidsmentioning
confidence: 99%
“…Another research study showed a mixture of Mn 3 O 4 and CaCl 2 to obtain a low-solid high-density drilling fluid. The experimental results showed that the addition of lignite, vinyl amide, and vinyl sulfonate copolymer prominently improves the rheological features and enhances fluid loss control . The key features of Mn 3 O 4 were exploited by combining with ilmenite to get ultrahigh-density drilling fluid with a density of 22.12 lb/gal.…”
Section: Oilfield Applications Of High-density Brinementioning
confidence: 99%